Eradication of Helicobacter pylori in patients without gastric symptoms suffering from recurrent aphthous stomatitis: A pilot study - Latković, Marina; Ranin, Lazar; Teodorović, Nevenka; Andjelković, Marko (Vojnosanitetski pregled, 2017)
Background/Aim. Helicobacter (H.) pylori is a widespread bacterium and its involvement in pathogenesis of gastric diseases is well-known. However, H. pylori role in etiology of other histologically similar conditions, especially recurrent aphthous stomatitis (RAS) is still controversial. Research regarding H. pylori and its association with RAS, as well as the treatment options were always conducted on patients with diagnosed gastric problems. The aim of this study was to determine whether H. pylori is present in the oral cavity of patients suffering from RAS but without any symptoms or medical history of gastric disease. Methods. A total of 15 patients with RAS participated in the study. None of the participants suffered from any gastrointestinal disorders. Two dental plaque samples from each participant were collected. The first was analyzed using rapid urease test and the second one was put in transport medium and sent for cultivation. The sensitivity of H. pylori to antibiotics was established using disk diffusion method of sensitivity testing for every patient individually and adequate therapy was prescribed. Results. Before the treatment the mean annual recurrence rate of RAS was 8.1 ± 2.1, with the average number of lesions being 3.9 ± 1.9. During the 12-month observation period after the eradication therapy, none of the patients reported recurrence of aphthous lesions. The treatment was successful in all cases. Conclusion. This study shows that RAS can be effectively treated by successful eradication of oral H. pylori, and that RAS could be possibly considered as an early warning sign of potential gastric infection by H. pilory.
Keywords: stomatitis; aphthous; recurrence; helicobacter pylori; comorbidity; diagnosis; treatment outcome